Jula juli bintang tiga - B. N. Rao ([S.l.] : Cathay-Keris Film [production company] ; Kuala Lumpur : Grand Brialliance [distributor])
Sebuah cerita melayu klasik
Copy available in DVD format
Penyunting, Hussain Haniff ; pengarah fotografi, N. B. Vasudev ; musik, Zubir Said
Salmah Ahamad, Abdullah Chik, Sheriff Medan, Umi Kalthoum, S. M. Wahid (Satay)
Keywords: Motion pictures -- Malaysia; Fairy tales -- Film and video adaptations; Malay drama